Metody aktywizacji pracowników stosowane w Volkswagen Motor Polska przez liderów w celu zarządzania jakością - Bobik, Dorota (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The term leader has significantly changed its meaning nowadays. Quite not long ago a person or some people were leaders who managed an organization. Today a leader is not only a president, a director or a manager. Every person involved in the development of a company has leadership responsibilities. Norm ISO 9001:2000 defines leadership as board of directors; however, it prefers modern methods of management. The standards operative in the automotive industry (VDA 6.1) make additional demands on a board of directors as far as the strategy of an organization is concerned. The term leadership is understood in the EFQM Excellence Model in a much broader sense (Criterium 1). The Model differentiates between formal and informal leaders. Norms ISO and the automotive standards concerning quality management are developing in the direction of the requirements of the EFQM Excellence Model. Norm ISO 9004:2000 "Quality Management Systems -Guidelines for Performance Improvements" bases the improvement of an organization on eight essentials of excellence. One of these essentials is "Leadership & Constancy of Purpose". VOLKSWAGEN has based its Quality Policy on these essentials and has adopted the idea of "teamwork". Teamwork gives the best employees, who follow ethical values of VW concern and using their leadership skills constantly inspire others, an opportunity of succeeding. There are two teams working according to these principles in VW, namely: a group coordinators responsible for the development of the quality management system and a group called ProMotor (the Project of the Motor Organization Development) implementing the EFQM Excellence Model. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1177, s. 67-79